A combined "ground support-rock modification-destressing" strategy for 1000-m deep roadways in extreme squeezing ground condition. (June 2021) - Kang, Hongpu; Jiang, Pengfei; Wu, Yongzheng; Gao, Fuqiang
Abstract: Deep underground coal mines face great challenges of extreme squeezing conditions resulting from high mining-induced stresses caused by a high recovery of the reserves and low to moderate strength coal measures. This is particularly true for deep roadways that suffer side and front abutment pressures. In this study, a case study was conducted in a 1000-m deep coal mine with extreme squeezing ground conditions. A new strategy of "ground support + rock modification + destressing" was proposed for the ground support. A numerical simulation was performed to evaluate the performance of the new support strategy. Field observations suggested that the proposed strategy could successfully mitigate the extreme squeezing of the double-used entry. The proposed support strategy provides an effective measure for ground control in extreme squeezing conditions.